2007
DOI: 10.1179/106698107791090150
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Management of Complex Regional Pain Syndrome I in a 14-Year-Old Patient Using Strain Counterstrain: A Case Report

Abstract: This report describes the examination, intervention, and outcomes for a patient with Complex Regional Pain Syndrome I (CRPS I) treated with Strain Counterstrain (SCS). The patient was diagnosed with CRPS I following a Grade II ankle sprain. Treatment consisted of SCS once per week for six months with one additional session each week in Months 4 through 6 for strengthening, endurance, and gait training. A re-examination was performed monthly. A clinically signifi cant decrease of 2 points in overall pain as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
(59 reference statements)
2
17
0
Order By: Relevance
“…Similar to my case report, Wynne et al [5] reported the immediate effect was more substantial than the lasting effect, which was significant [5]. Additional studies are suggested to assess the temporal aspect of symptom relief from S-CS [3,5,7]. In a case report on S-CS for a 14-year old with Complex Regional Pain Syndrome, Collins [7] reported pain reduction for up to three days post-intervention and an overall improvement over the six months of treatment for the patient in their case [7].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar to my case report, Wynne et al [5] reported the immediate effect was more substantial than the lasting effect, which was significant [5]. Additional studies are suggested to assess the temporal aspect of symptom relief from S-CS [3,5,7]. In a case report on S-CS for a 14-year old with Complex Regional Pain Syndrome, Collins [7] reported pain reduction for up to three days post-intervention and an overall improvement over the six months of treatment for the patient in their case [7].…”
Section: Discussionsupporting
confidence: 67%
“…Additional studies are suggested to assess the temporal aspect of symptom relief from S-CS [3,5,7]. In a case report on S-CS for a 14-year old with Complex Regional Pain Syndrome, Collins [7] reported pain reduction for up to three days post-intervention and an overall improvement over the six months of treatment for the patient in their case [7]. Future studies may investigate the duration of symptom reduction after S-CS to determine an optimal plan of care for patients with pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research on the efficacy of S-CS in affecting positive changes in pain and strength in the foot [4,5], hip [2], low back [6], and for neurological conditions such as complex regional pain syndrome [3] have been reported. See Table 1 for a summary of the research.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the efficacy of S-CS as an effective primary intervention or adjunct to modalities, mobilization, or therapeutic exercise has been problem-some for practitioners due to the lack of interventionspecific S-CS research. Prior research has demonstrated that S-CS decreases pain [1][2][3][4][5], improves strength [2], increases mobility, improves function, and decreases disability [3,6]; however, none of the studies have described the application of S-CS for musculoskeletal-related cervical pain [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%